2024
DOI: 10.1088/1475-7516/2024/02/054
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dark Matter density with gravitational waves from super-massive binary black holes

Anish Ghoshal,
Alessandro Strumia

Abstract: Supermassive black hole binaries source gravitational waves measured by Pulsar Timing Arrays. The frequency spectrum of this stochastic background is predicted more precisely than its amplitude. We argue that Dark Matter friction can suppress the spectrum around nHz frequencies, where it is measured, allowing to derive robust and significant bounds on the Dark Matter density, which, in turn, controls indirect detection signals from galactic centers. A precise spectrum of gravitational waves would tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In addition to placing competitive constraints on modified gravity, a more ambitious possibility is to invoke slow-motion, beyond-GR effects to alleviate or solve the tension in the latest PTA data if the detected SGWB is interpreted as arising from SMBH binaries. While we showed that this is in principle possible without violating current constraints, one should be careful with degeneracies with astrophysical effects [13][14][15][16][17][18][19]21], including large eccentricity [106,107], and environmental modifications such as stellar scattering, interaction with circumbinary gas, and dynamical friction [16,20,105]. In this context, since our framework can accommodate both beyond-GR and environmental effects, it can be used to disentangle these modifications (which often enter at different negative PN order) through dedicated Bayesian inferences with more constraining future datasets.…”
Section: Jcap04(2024)056mentioning
confidence: 84%
See 2 more Smart Citations
“…In addition to placing competitive constraints on modified gravity, a more ambitious possibility is to invoke slow-motion, beyond-GR effects to alleviate or solve the tension in the latest PTA data if the detected SGWB is interpreted as arising from SMBH binaries. While we showed that this is in principle possible without violating current constraints, one should be careful with degeneracies with astrophysical effects [13][14][15][16][17][18][19]21], including large eccentricity [106,107], and environmental modifications such as stellar scattering, interaction with circumbinary gas, and dynamical friction [16,20,105]. In this context, since our framework can accommodate both beyond-GR and environmental effects, it can be used to disentangle these modifications (which often enter at different negative PN order) through dedicated Bayesian inferences with more constraining future datasets.…”
Section: Jcap04(2024)056mentioning
confidence: 84%
“…This range becomes even wider for more negative PN corrections. Note that this general formalism includes several classes of gravity theories [90], but also several environmental effects that provide dissipation mechanisms at negative PN orders [102][103][104], leading to a steeper scaling [16,20,105]. Examples include accretion and dynamical friction (q = −5.5), stellar scattering (q = −5), and interaction with circumbinary gas (q = −3.5).…”
Section: Jcap04(2024)056mentioning
confidence: 99%
See 1 more Smart Citation
“…While supermassive black hole binary (SMBHB) mergers can, in principle, generate such a signal, albeit with mild tension, plenty of scopes exist for exotic new physics [5]. Several follow-up papers have also studied the possible origin or implications of this observation from the point of view of DM [6,7], axions or axion-like particles [8,9], SMBHB [10], first-order phase transition [11][12][13][14], primordial black holes [15], topological defects [16][17][18][19], inflation [20] among others [21][22][23].…”
Section: Introductionmentioning
confidence: 99%